P05.38 Stereotactic radiosurgery of benign brain tumors in elderly patients: Evaluation of clinical outcome and toxicity. (19th September 2018) - Daniel, R; Weyer, V; Hoevels, M; Grau, S; Jablonska, K; Tutunji, J; Kocher, M; Treuer, H; Ruge, M
Abstract: Background: Stereotactic radiosurgery (SRS) is widely accepted as a therapeutic option for benign brain tumors such as meningioma and neurinoma; however, detailed data on outcomes and toxicity especially in the elderly population have not yet been reported. Material and Methods: In this single center retrospective analysis we consecutively included all patients aged ≥ 60 years with benign intracranial tumors (meningiomas, neurinomas) who underwent single fraction SRS by use of modified linear accelerator (LINAC) or Cyberknife® between 1991 and 2018. Patient data were analyzed in terms of tumor control (defined as no further intervention required), symptom control (stable clinical condition), co-morbidities and incidence of early and late treatment related complications (rated by using the Common Terminology Criteria for Adverse Events, CTCAE; v4.03). Results: We identified 224 patients with either vestibular schwannoma (n=147) or meningioma (n=77). The median age was 68 yr (range, 60–84 yr), and the mean and median follow-up were 55 and 41 mo (range, 2–227 mo), respectively. Tumor margins were irradiated with a median dose of 12 Gy (range, 10–18.7 Gy), and the median tumor volume was 2.3 ml (range, 0.1–23.7 ml). Actuarial local tumor control rates at 2, 5, and 10 yr after SRS were 98%, 94%, and 90%, respectively. Mild or moderate adverse events were noted in 41 cases (18%). No severe adverse event was observed during early and late follow up. Conclusion: SRS provides favorable tumor control and a low risk of treatment related adverse early and/or late events. Thus, SRS should be taken into account as treatment option for benign intracranial tumors in elderly patients.